Pemenuhan Kebutuhan Pendidikan bagi Penyandang Disabilitas di Kota Bandung - Islam, Anshori Daulatul; Timorochmadi, Ferry; Fakhrudin, M.Y.; Yoseptry, Ricky; Ratnawulan, Teti; Rahayu, Neni Sri (STKIP PGRI SITUBONDO, 2024)
Data shows that efforts to fulfill educational rights for people with disabilities are still not optimal. This can be seen from statistical data published by the Coordinating Ministry for Human Development and Culture in June 2022, the number of people with disabilities among children aged 5-19 years reached around 3.3%. According to data from the Bandung City Social Service, it shows that in Bandung City there are more than 8,600 people with disabilities. If we refer to the Ministry of Education and Culture's data that only 12.26% of people with disabilities have received education, then only around 1,032 people with disabilities have received their right to education. The aim of this research is to determine the fulfillment of educational needs for people with disabilities in Bandung City and to determine the implementation of the policy for fulfilling education for people with disabilities in education units. The method applied in this research is a qualitative descriptive method. The research location is at the Bandung City Education Office, Jl. A. Yani No. 239, Merdeka, Kec. Sumur Bandung, Bandung City, West Java 40113 and Al-Biruni Science Elementary School, Komp. Bumi Panyileukan Jl. Raya Panyileukan No.11, Cipadung Kidul, Kec. Panyileukan, Bandung City, West Java 40614. The conclusions of this research are (1) the Education Office has issued a policy regarding meeting the educational needs of people with disabilities in Bandung City and (2) the education unit has implemented this policy by accommodating the acceptance of students with special needs (PDBK).